The Epic Hero - Miller, Dean A. (Book collections on Project MUSE., 2002)
"Drawing on diverse disciplines including classics, anthropology, psychology, and literary studies, this product of twenty years' scholarship provides a detailed topology of the hero in western myth: birth, parentage, familial ties, sexuality, character, deeds, death, and afterlife. Dean A. Miller examines the place of the hero in the physical world (wilderness, castle, prison cell) and in society (among monarchs, fools, shamans, rivals, and gods). He looks at the hero in battle and quest; at his political status; and at his relationship to established religion. The book spans western epic traditions, including Greek, Roman, Nordic, and Celtic, as well as the Indian and Persian legacies. A large section of the book also examines the figures who modify or accompany the hero: partners, helpers (animal and sometimes monstrous), foes, foils, and even antitypes."--Jacket.